2019
DOI: 10.1002/art.40919
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors in Statin‐Associated Immune‐Mediated Necrotizing Myopathy: A Case Series

Abstract: Objective. To determine the safety of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in patients with statin-associated anti-3-hydroxy-3-methlyglutaryl coenzyme A reductase (anti-HMGCR)-positive immunemediated necrotizing myopathy (IMNM).Methods. Muscle strength was assessed in anti-HMGCR-positive patients at each visit before and after initiation of PCSK9 inhibitors. The trends in creatine kinase (CK) levels and serum anti-HMGCR antibody titers were monitored over time.Results. Among 122 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“… 18 Cycles of every 2 weeks to 4 weeks have been reported during maintenance therapy, and can be stopped and tapered as tolerated. 19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 18 Cycles of every 2 weeks to 4 weeks have been reported during maintenance therapy, and can be stopped and tapered as tolerated. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Statin rechallenge with the same or a different statin has shown to be largely unsuccessful and often results in disease flare up. 19 , 6 A recent case series at Johns Hopkins University found that PCSK9 inhibitors were well tolerated in 7 out of 8 patients with a previous history of statin-induced IMNM. 19 As a result PCSK9 may be an alternative medication for patients with high cardiovascular risk and IMNM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She improved with steroids and her symptoms were minimal on follow-up. As far as alternative options for cholesterol management in patients with SAAM, we can consider PCSK9 inhibitors such as Praluent (alirocumab) and Repatha (evolocumab) [15].…”
Section: Figure 1: Muscle Biopsymentioning
confidence: 99%
“…For patients with anti-HMGCR antibodies, cessation of statin therapy is important [ 54 ]. For patients that require cholesterol-lowering medication, proprotein convertase subtilisin/kexin type 9 (PCSK9) can be considered, as these medications were shown to be safe in a case series of 8 patients with HMGCR antibody-positive necrotizing myopathies [ 55 ]. In rare mild cases, further treatment beyond statin cessation may not be necessary [ 54 ].…”
Section: Treatment Of Secondary Myositismentioning
confidence: 99%